PENINGKATAN KEMAMPUAN MENGHITUNG BILANGAN BULAT POSITIF DAN NEGATIF DENGAN MENGGUNAKAN MEDIA GARIS BILANGAN PADA SISWA KELAS VI UPTD SDN BANYUAJUH 5 - Aini Syarifa; Agung Setyawan (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
Mathematics education in class VI UPTD SDN Banyuajuh 5 academic year 2022/2023 is not satisfactory because the average result of the concept test regarding positive and negative integers is 60, which is less than the minimum criteria for passing, namely 65. In addition, students often feel afraid in studying mathematics. The aim of the research was to find out the use of instructional media to improve the ability to count positive and negative integers in mathematics for class VI students of UPTD SDN Banyuajuh 5 Year 2022/2023 or not. This type of study is Classroom Action Research (action research). [1] classroom action research is research conducted by educators in classrooms and involves collaboration between researchers and practitioners such as teachers and school principals. The research procedure consisted of two stages (cycle I and cycle II) with each stage covering problem identification, planning, implementing actions and observing, as well as reflecting and changing plans. The purpose of this classroom action research was to determine the effectiveness of using number line learning media in improving the ability of class VI students at UPTD SDN Banyuajuh 5 in calculating positive and negative integers. The results in the first cycle of students' ability to calculate integers have shown improvement, but not in accordance with the expectations of researchers. After discussing data analysis and learning mathematics, especially counting positive and negative integers using a number line, Cycle II showed significant changes. It can be seen that student participation in learning increases with more intensive activities. Students enthusiastically pay attention to and answer teacher questions and are more active in showing initiative and creativity.